Unequal Britain : Equalities in Britain Since 1945. - Thane, Pat (Bloomsbury Publishing, 2010)
That people should be treated as equals is one of the core principles that underpin our society. Philosophers and social theorists have long debated what equality is, and this book probes what this means for both those at the centre and on the margins of society. Britain is in many ways a fairer and more equal society today than at any other time in living memory. One hundred years ago women were not allowed to vote: this seems preposterous now. It is an undeniable truth, however, that inequalities still persist today. In some cases they seem to grow. Prejudice is apparent in everyday life, and flares up from time to time on a national scale. From Brixton to Bradford, history is littered with examples. This book engages with key issues today, and engages with how far we have come as a society facing up to difficulties of the past and more recent challenges. It goes on to explore ways forward to ensure that we remain an open and tolerant society.